Design of a new on-off controller based on Arduino UNO R3 with application to Window A/C - E Erham; Markus Markus; W P Sopianti (Institut Teknologi Sepuluh Nopember, 2018)
Window Air Conditioner (A/C) is air conditioning which services need of thermal comfort inside a small or medium room. To maintain the desired temperature, then A/C employs the thermostat that functions as an on-off controller. In general, it works based on the set point and the control differential; however the differential is not available to set. In fact, the differential has a quite important role . In this paper was proposed a new optional controller based on an Arduino UNO R3 so that the differential can be also set. In addition, it is aimed to anticipate if the thermostat has a problem. Based on these purposes, then it was designed an on-off controller and the thermostat was replaced by using the Arduino in which was uploaded the algorithm of controller. However, the excellence of device can be tested in A/C without uninstalling the existing thermostat. The response of control system obtained is appropriate with design objectives. Although, it at crucial time points still has a response error with range from 0.020C to 0.38oC.Thus, it is more accurate than a conventional system whose error from 0.5°C to 0.95°C. Moreover, the designed controller can reduce the energy consumption of about 66% compared to the thermostat.